2010
DOI: 10.1007/s10228-010-0161-7
|View full text |Cite
|
Sign up to set email alerts
|

Current status and ecological characteristics of the Chinese temperate bass Lateolabrax sp., an alien species in the western coastal waters of Japan

Abstract: A total of 263 adult and preadult Chinese temperate bass Lateolabrax sp. caught at 20 locations in the coastal waters of western Japan from October 1999 to September 2008 were used for age, growth and maturity examinations. Examination of marginal increments of transverse sections of otoliths showed that rings (opaque zones) were formed once a year from spring to summer. According to the number of rings and the sampling month, ages were assigned to individuals. For males, we obtained the following von Bertalan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…In fact, Lou et al (2002), who compared morphology between L.japonicus (1 sample lot from Tokyo, Japan) and L.maculatus (5 sample lots from Beihai, Xiamen, Fuzhou, Zhoushan and Weihai, China), showed considerable range overlaps for LLS and TGR counts, although the average values of those counts for L.maculatus were unequivocally lower than those for L.japonicus . Although Iseki et al (2010) identified 263 Lateolabrax specimens from western Japan as L.maculatus (as L. sp.) based on LLS and gill raker counts proposed by Yokogawa and Seki (1995), some difficulties in identification may have been encountered due to some of their specimens being very large (up to 1130 mm SL), with gill raker counts that approached or overlapped the range for L.japonicus .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Lou et al (2002), who compared morphology between L.japonicus (1 sample lot from Tokyo, Japan) and L.maculatus (5 sample lots from Beihai, Xiamen, Fuzhou, Zhoushan and Weihai, China), showed considerable range overlaps for LLS and TGR counts, although the average values of those counts for L.maculatus were unequivocally lower than those for L.japonicus . Although Iseki et al (2010) identified 263 Lateolabrax specimens from western Japan as L.maculatus (as L. sp.) based on LLS and gill raker counts proposed by Yokogawa and Seki (1995), some difficulties in identification may have been encountered due to some of their specimens being very large (up to 1130 mm SL), with gill raker counts that approached or overlapped the range for L.japonicus .…”
Section: Discussionmentioning
confidence: 99%
“…However, morphological and genetic work on Lateolabrax specimens introduced from China to Japan has demonstrated that they are not L. japonicus but a distinct species (Yokogawa and Seki 1995;Yoko gawa et al 1996;Yokogawa 2002;Iseki et al 2010), which has recently been identified as the spotted sea bass L. maculatus (Yokogawa et al 2013). The sampling localities of the fish infected with the three dactylogyrids in China were the Liaoho River flowing into the Bohai Sea, the Yellow Sea (Gussev 1967), and four provinces (Liaoning, Zhejiang, Hubei, and Guangdong) (Chen 1984;Wu and Wang, 1991;Zhang et al 1992Zhang et al , 2001Wu 2000aWu , 2000bDing and Liao 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It has escaped from culture cages and spread to some Japanese coastal waters (Ui 1998;Hirota et al 1999;Wakabayashi and Nakamura 2003;Iseki et al 2010). The myxozoan Henneguya lateolabracis Yokoyama, Kawakami, Yasuda and Tanaka, 2003, which caused fish mortalities, was found in L. maculatus immediately after this fish had been brought to Japan (Yokoyama et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…sp., are distributed in Tango Bay, L. sp. is an introduced species that is unlikely to reproduce on the Sea of Japan side (Iseki, Mizuno, Ohta, Nakayama, & Tanaka, ). On the other hand, L. japonicus and L. latus have little overlap in the hatching season in Tango Bay (January–February and March–April, respectively; Y. Yube, S. Harada, M. Hibino, & M. Tanaka, unpublished), hardly co‐occurring during the planktonic period.…”
Section: Methodsmentioning
confidence: 99%
“…sp., are distributed in Tango Bay, L. sp. is an introduced species that is unlikely to reproduce on the Sea of Japan side (Iseki, Mizuno, Ohta, Nakayama, & Tanaka, 2010 co-occurring during the planktonic period. In the present study, eggs and larvae that were identified as Lateolabrax spp.…”
Section: Sample Analysismentioning
confidence: 99%